Tribotest of engine piston ring/cylinder liner pairs with different nanoparticles added into engine oil - Demirtas, Selman; Kaleli, Hakan; Khadem, Mahdi; Kim, Dae-eun (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose Wear on internal combustion engines is a loss of material that occurs with the rubbing of the materials in contact with each other and significantly reduces the economic life of the engine. Even the smallest precaution that can be taken to prevent friction and wear in the engines can provide economical savings in very large quantities. Internal combustion engines are widely utilized in modem automobiles. Around 10 per cent of the total fuel energy is dissipated to heat due to mechanical friction, among which 20 per cent is caused by the contact between the cylinder liner and the piston rings. Design/methodology/approach In this study, real piston ring-cylinder specimens were tested with reciprocating tribometer by using five different nanoparticles added to engine oil to investigate their wear and friction behavior. Findings With regard to the experiments, it has been found that the best results were determined by TiO2 and single-walled carbon nanotubes according to boron nitride, multi-walled carbon nanotubes and graphene nanoparticles added to the engine oil, respectively. At the end of the tests, different wear mechanisms have been determined after the surface analyses on the piston ring and cylinder liner surface, and abrasive wear has been observed as the main wear mechanism. Originality/value This paper has an originality with regard to adding different nanoparticles into the commercial engine oil.
Keywords: Nanoparticles; Wear; Friction; Engineering